Synthesis of new N-Substituted -3- chloro -2- azetidinones for 2, 4-Diamino-6-phenyl-1,3,5-triazine (Journal of the College of Basic Education, 2023)
The current study involved synthesis of several new N-Substituted -3- chloro -2- azetidinones for 2,4-Diamino-6-phenyl-1,3,5-triazine by twosteps. The first step includes preparation of Schiff bases (Al-A6) bycondensation of 2,4-Diamino-6-pheny]-1,3,5-triazine with many substitutedaldehydes, then the second step includes preparation new six azetidinonecompounds (B1-B6) by reaction of chloro acetyl chloride with theprepared Schiff bases in first step. The prepared compounds werecharacterized by physical properties, FT-IR, UV and some of them by 'H-NMR, "C-NMR spectroscopy were recorded.